Questionnaire Survey Medical Futility and Termination of Resuscitation in Out-of-hospital-cardiac-arrest Patients Presenting to Emergency Department in Hospitals in Klang Valley - Nur Aiza Mohamed Salleh; Khadijah Poh; Hafizah Zainal Abidin; Teh Yong Hup Teh (Eurasian Journal of Emergency Medicine, 2023)

(untitled)
Aim:The knowledge and understanding of medical futility and decisions about termination of resuscitation (TOR) for out-of-hospital cardiac arrest (OHCA) are highly heterogeneous and dependent on the practice and beliefs of the attending emergency physicians. The objective of this study was to determine current practice, knowledge and attitude among emergency medical practitioners regarding medical futility and termination of cardiopulmonary resuscitation (CPR) in OHCA patients in Hospital Ampang, Pusat Perubatan University Malaya, Hospital Kuala Lumpur and Hospital Serdang.Materials and Methods:A cross-sectional survey was conducted among medical practitioners in emergency departments in the Klang Valley. The questionnaire assessed the participants’ demography, knowledge, attitudes and behaviors (KAB) about TOR of OHCA and identification of medical futility. Subgroup analysis regression analysis was used to identify the relationship between respondents’ demography, KAB.Results:The sample size of this survey was 152 taken at 90% confidence interval. Results show that those with more than 5 years of experience in emergency medicine (EM) had a higher attitude score compared to those with less than 1-year experience (p<0.001) and 1-5 years’ experience (p=0.003). The behavior composite score was statistically significant between those with less than 1 year of EM experience and 1-5 years of EM experience (p=0.042). Respondents who called off unsuccessful CPR were associated with higher attitude and behavioral composite scores (p<0.05).Conclusion:Behavior and practice on TOR do not have any association with the clinician’s knowledge. However, more learning activities need to be done to empower medical practitioners on the medical futility of resuscitation and to understand the criteria for the termination of resuscitation.